Firm Size and Business Risk on Debt Policy with Profitability as Moderating Variables - Shifa Hanida Shifa; Iis Ismawati; Mukhtar Mukhtar; Nurhayati Soleha; Ina Indriana (Journal of Applied Business, Taxation and Economics Research, 2022)
This study aims to examine the effect of firm size and business risk on debt policy with profitability as a moderating variable. The proxy for company size uses Natural Logarithms (Total Assets), business risk uses net income to total equity, and profitability uses Return On Assets (ROA). The population used in this study is property and real estate companies listed on the Indonesia Stock Exchange for the 2018-2020 period. This research uses quantitative research with multiple linear regression model. By using purposive sampling, 55 companies were found that met the criteria as research samples. This study uses secondary data obtained from the Indonesia Stock Exchange and sample company websites. The analytical method used in this study is Moderated Regression Analysis (MRA) using the Eviews 9 application. The results of this study indicate that company size and business risk have a positive and significant effect on debt policy. Profitability as a moderating variable is proven that profitability weakens the relationship between firm size and debt policy, while profitability strengthens the relationship between business risk and debt policy.